Extracellular signal-regulated kinase, substance P and neurokinin-1 are involved in the analgesic mechanism of herb-partitioned moxibustion - Li, Zhi-yuan; Yang, Yan-ting; Hong, Jue; Zhang, Dan; Huang, Xiao-fei; Wu, Li-jie; Wu, Huan-gan; Shi, Zheng; Liu, Jie; Zhu, Yi; Ma, Xiao-peng (Neural regeneration research, 2017)
Herb-partitioned moxibustion can effectively mitigate visceral pain, a major symptom in inflammatory bowel disease, but the analgesic lnechanism is still unclear. Moreover, extracellular signal-regulated kinase, substance P, and neurokinin-1 are involved in formation of central hyperalgesia. Thus, we postulated that the analgesic effect of herb-partitioned moxibustion may be associated with these factors. Accordingly, in this study, we established an inflammatory bowel disease visceral pain model in rat by enema with a mixed solution of 5% trinitrobenzenesulfonic acid and 50% ethanol. Bilateral Tianshu （ST25） and Qihai （CV6） points were selected for herb-partitioned moxi- bustion. Our results showed that herb-partitioned moxibustion improved visceral pain and down-regulated extracellular signal-regulated kinase, substance P, and neurokinin-1 protein and mRNA expression in dorsal root ganglia. These results indicate that down-regulation of extracellular signal-regulated kinase, substance E and neurokinin-1 protein and mRNA may be a central mechanism for the analgesic effect of herb-partitioned moxibustion.